Introduction - De Filippo, Massimo (Acta Biomedica Atenei Parmensis, 2016)
This special issue covers important and controversial topics in radiology. Each topic addressed presents important viewpoints from leading radiologists. High-quality reproductions of radiographs, CT scans, MR images, and sonograms clearly depict what is being described in each article. This articles offer an outstanding, time-saving investigation into some current topics most relevant to radiologists.